Methodical instructions to perform independent work in the discipline "Financial diagnostics in anticrisis management" - Yurieva, Iryna; Tkachenko, M. O. (National Technical University "Kharkiv Polytechnic Institute", 2024)
Modern enterprises become most vulnerable in the event of a crisis caused by economic, financial, technological and other factors. In view of this, enterprises should actively use all modern tools of various methods of financial analysis, which are the basis for qualitative diagnostics of the crisis state. At the same time, systematic diagnostics of the financial condition in crisis management. The discipline "Diagnostics of Financial Condition in Crisis Management" examines the methods of assessing the financial condition of an enterprise in crisis management. In addition, the course provides tools for analytical diagnostics of the possible emergence of negative phenomena in economic activity that may lead to bankruptcy in order to develop measures aimed at improving the financial condition of the enterprise and crisis management. The practical application of this discipline consists in discussing discussion issues in classroom classes, as well as performing practical exercises that develop skills in assessing and analysing the financial and economic condition of the enterprise, its effective management, taking into account the conditions of its activities in a state of crisis of varying degrees of severity, as well as solving problematic issues of crisis management. The subject of the discipline is the methodology and tools for applying financial and economic analysis approaches in crisis management of national economy sectors. The programme of the discipline consists of two substantive modules: Module 1 "Problems of financial diagnostics in crisis management of an enterprise" and Module 2 "Analytical tools for financial diagnostics of the enterprise".
Keywords: methodical instructions; economic activity; finance; modern enterprises; crisis; management